Impact of renal allograft nephrectomy on graft and patient survival following retransplantation: a systematic review and meta-analysis. Issue 4 (12th February 2018) - Lin, Jinwen; Wang, Rending; Xu, Ying; Chen, Jianghua
Abstract: Background: It is not clear whether renal allograft removal affects the outcome of renal retransplantation. This study aimed to determine the effect of allograft nephrectomy (AN) and no-AN (No AN) on renal retransplantation. Methods: A systematic review and meta-analysis were conducted using MEDLINE, Embase and the Cochrane Library. Observational studies or randomized controlled trials including renal retransplantation recipients with AN or No-AN were included. The primary outcomes were graft survival, patient survival, acute rejection (AR) and delayed graft dysfunction; the secondary outcomes were positive panel reactive antibody rate and serum creatinine level at 1 year after retransplantation, cold ischemia time and time of hemodialysis before recent transplantation. Pooled estimates of odds ratios (ORs) and the weighted mean difference for outcomes were calculated. Results: A total of 13 studies divided into 20 trials including 1923 patients were analyzed. The No-AN group had a significantly higher 3-year graft survival rate {OR 0.48 [95% confidence interval (CI) 0.34–0.69], 10 studies, n  = 1030} and 5-year graft survival rate [OR 0.65 (95% CI 0.44–0.97), 16 studies, n  = 1878] than the AN group. The rates of 5-year patient survival [OR 1.82 (95% CI 1.14–2.90), 5 studies, n  = 749], positive panel reactive antibody [OR 3.08 (95% CI 2.08–4.56), 12 studies, n  = 1225], AR [OR 1.59 (95% CI 1.21–2.09), 15 studies, n  = 1388] and delayed graft dysfunction [OR 1.66 (95% CI 1.20–2.03), 8 studies, n  = 879] were all significantly higher in the AN group. Compared with the No-AN group, cold ischemia time was longer in the AN group [weighted mean difference 1.84 (95% CI 0.90–2.79), 7 studies, n  = 919]. The rate of 1-year graft survival and 10-year graft survival, serum creatinine levels at 1 year after retransplantation and the time of hemodialysis before recent transplantation were similar between the AN and No-AN groups. Conclusions: We recommend allowing the failed graft to remain unless symptoms dictate the need for surgery. We also suggest donor-specific antibody dynamic monitoring and better human leukocyte antigen matching for improved long-term outcome of retransplantation.